The juggling act of pharmacists in Sweden: a qualitative study on balancing healthcare professionalism and retail employment - Kenneth Hagsten; Andrea Eriksson; Ingrid Svensson; Kristina Palm (BMC, 2024)
Abstract Background Community pharmacies in Sweden merge a state-funded professional community service with a retail business. While previous research has recognized its challenges, less attention has been paid to the potential conflict of interest it could result in regarding the work of pharmacists. This study aims to increase understanding of how pharmacists in Sweden combine their healthcare ambitions and obligations with those concerning being employees in a retail business. Methods Semi-structured interviews were conducted with 28 pharmacists employed by pharmacy chains in Sweden. The data were thematically analysed. Results In the analysis, three themes were formulated: Different interests, The conflict between professional work & business work, and Strategies to manage the conflicts. The analysis of the data reveals that pharmacists in Sweden experience a conflict of interest. They grapple with balancing being healthcare professionals with a focus on patient care and being valued retail employees that also focus on financial results. This conflict manifests in various situations, such as time management, communication focus, preferred behaviours, and different tasks. The different strategies applied by individual pharmacists to manage the work are results of job crafting. Pharmacists employ strategies such as compromise, mandate stretching, avoidance, and acceptance to manage the conflict. However, these strategies lead to compromises in their work. Conclusion This study aimed to understand how pharmacists combine their healthcare ambitions and obligations with those of being employees in a retail business. The study demonstrated that Swedish community pharmacists need to perform a juggling act to be both professional healthcare workers and viewed as valuable retail employees. In situations when the conflict of interest occurs, the pharmacists use different strategies when determining how to prioritize between the professional work and the business work. The conflict of interest in the pharmacists' work need to be taken into consideration when discussing pharmacists practices, the profession, or role it's in the healthcare system.